PENGARUH JUMLAH ULASAN, RATING REVIEW ONLINE DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK MAYBELLINE PADA MARKETPLACE LAZADA - Hapsari May Indriani; Wulan Purnamasari (widya balina, 2025)
This study aims to analyze the influence of the number of reviews, online review ratings, and price on the purchasing decisions of Maybelline cosmetic products on the Lazada marketplace, using a case study of consumers in Wringinanom. The rapid development of digital technology has transformed consumer behavior in online shopping, where customer reviews and ratings have become essential considerations before making a purchase. Additionally, price plays a crucial role in influencing final purchase decisions. This research uses a quantitative approach with an explanatory research type. Data were collected through questionnaires distributed to 96 respondents who had purchased Maybelline products on Lazada. The data analysis techniques used include validity and reliability tests, multiple linear regression, t-test, F-test, and the coefficient of determination, processed with SPSS version 25. The results indicate that partially, the number of reviews, online review ratings, and price significantly influence purchasing decisions. Simultaneously, all three variables have a significant impact on purchasing decisions for Maybelline products on the Lazada marketplace. These findings provide important implications for online businesses to pay closer attention to customer reviews and pricing strategies to better influence consumer purchase behavior.